Ateroscleróticos hipertensos e os polimorfismos dos genes eNOS (G894T e T786C), GSTT1 e GSTM1 - Morais, Monize Prado de (2016)
The atherosclerosis is a multifactorial chronic inflammatory disease that occurs in response to the endothelial aggression, compromising the intimate layer of media and large caliber arteries. The systemic arterial hypertension is considered the main risk factor for the formation of atherogenic plates, increasing the risk of cardiovascular events between two and three times. Several genes are involved in the process of atherogenesis and hypertension, this research studies some polymorphisms for candidates genes that participates in the process which involves both pathologies, the polymorphisms G894T and T-786C of the genes eNOS, and the polymorphisms of the genes GSTT1 and GSTM1. The objective of this work was to analyze and associate such polymorphisms in hypertensives atherosclerotics individuals and in individuals with absence of hypertension and atherosclerosis. This study deals with the control-case in which 267 samples were analyzed, of which 100 of control group and 167 of the group case. The samples were submitted to DNA extraction, then to PCR and analyzed in 1,5 % agarose gel, stained with ethidium bromide at 5µg/mL. Soon after, the results were compared using the Chi-Square test and the G-test. The results point to a prevalence of genotype GT (76%) and the mutant allele T (56%) of the polymorphism T786C (eNOS), with the p equal to 0.03. For the polymorphism T786C eNOS, the heterozygote genotype (TC) represented 58% of the sample, with the allele C prevailing with 61%, but there was no significant statistics. In the analysis of the gene GSTT1 prevailed the present genotype (84%) as well as the presence of GSTM1 (73%), in both associations the p detected was less than 0.05. Smoking association was found only in the polymorphism GSTM1. Regarding to alcoholism, there was only association between GSTT1 and the habit of drinking. There are many possible interactions of these polymorphisms and the development of atherosclerosis and hypertension, but more studies are necessary for further elucidation of these associations.